On the solubility and lipophilicity of metallacarborane pharmacophores - Rak, Jakub; Dejlová, Barbora; Lampová, Hana; Kaplánek, Robert; Matějíček, Pavel; Cígler, Petr; Král, Vladimír (Molecular pharmaceutics, 2013)
Metallacarborane moieties have been identified as promising pharmacophores. The pharmaceutical use of such compounds is, however, complicated by their low solubility and tendency to self-assemble in aqueous solution. In this work, we estimated the solubilities of a vast series of metallacarboranes [cobalt bis(dicarbollide) derivatives] in pure water, saline, and saline with human serum albumin as a model of blood plasma. In addition, we determined the octanol-water partition coefficients (Pow) as a lipophilicity descriptor. Pow weakly correlates with the water solubility of metallacarboranes, whereas the ability of HSA to increase the solubility of metallacarboranes correlates well with their Pow values. Because metallacarboranes are known inhibitors of HIV protease, the possible correlation between Pow and the ability to inhibit HIV protease was investigated. Results from this study indicate that interaction of metallacarborane inhibitors with HIV protease is driven by specific binding rather than by promiscuous lipophilic interactions. The most promising candidates for further drug development were identified by ligand lipophilicity efficiency analysis.
Keywords: kobalt; sloučeniny boru; HIV Protease Inhibitors; Humans; Molecular Structure; sérový albumin; organokovové sloučeniny; Cobalt; Lipids; inhibitory HIV-proteasy; Ligands; Solubility; Boron Compounds; ligandy; lidé; Serum Albumin; Organometallic Compounds; objevování léků; Drug Discovery; rozpustnost; molekulární struktura; lipidy